Association study of genes related to bone formation and resorption and the extent of radiographic change in ankylosing spondylitis. Issue 7 (20th March 2014) - Cortes, A; Maksymowych, W P; Wordsworth, B P; Inman, R D; Danoy, P; Rahman, P; Stone, M A; Corr, M; Gensler, Lianne S; Gladman, D; Morgan, A; Marzo-Ortega, H; et al.
Abstract : Objective: To identify genetic associations with severity of radiographic damage in ankylosing spondylitis (AS). Method: We studied 1537 AS cases of European descent; all fulfilled the modified New York Criteria. Radiographic severity was assessed from digitised lateral radiographs of the cervical and lumbar spine using the modified Stoke Ankylosing Spondylitis Spinal Score (mSASSS). A two-phase genotyping design was used. In phase 1, 498 single nucleotide polymorphisms (SNPs) were genotyped in 688 cases; these were selected to capture >90% of the common haplotypic variation in the exons, exon–intron boundaries, and 5 kb flanking DNA in the 5′ and 3′ UTR of 74 genes involved in anabolic or catabolic bone pathways. In phase 2, 15 SNPs exhibiting p<0.05 were genotyped in a further cohort of 830 AS cases; results were analysed both separately and in combination with the discovery phase data. Association was tested by contingency tables after separating the samples into 'mild' and 'severe' groups, defined as the bottom and top 40% by mSASSS, adjusted for gender and disease duration. Results: Experiment-wise association was observed with the SNP rs8092336 (combined OR 0.32, p=1.2×10 −5 ), which lies within RANK (receptor activator of NFκB), a gene involved in osteoclastogenesis, and in the interaction between T cells and dendritic cells. Association was also found with the SNP rs1236913 in PTGS1 (prostaglandin-endoperoxide synthase 1, cyclooxygenase 1), giving an OR of 0.53 (p=2.6×10 −3 ). There was no observed association between radiographic severity and HLA-B*27 . Conclusions: These findings support roles for bone resorption and prostaglandins pathways in the osteoproliferative changes in AS.